Washington View: Lessons from Benjamin Franklin. (April 2019) - Ferguson, Maria
Historian Nick Bunker's Young Benjamin Franklin: The Birth of Ingenuity shows that young Franklin benefited from a childhood with an ambitious and loving family, access to educational opportunities, and free time to explore. Maria Ferguson considers how those lessons might apply to contemporary childhoods. From a policy perspective, Franklin's childhood depended on strong early childhood education, access to higher education, and social and emotional learning. In all three areas, positive steps are being made, although progress is slow .